Indonesian National Defense Strategy in the Asean Region of the 21st Century Based on Defense System and Security Population Demography - Manurung, Yanto S; Maarif, Syamsul; Toruan, Tahan Samuel Lumban; Swastanto, Yoedhi (Graduate Program Magister Manajemen Pendidikan, 2023)
Given its strategic position between the Indian and Pacific Oceans, Indonesia has a very significant strategic interest and role in shaping the ASEAN Region. The proximity of Indonesia's position to one of the main conflict flashpoints in the ASEAN Region, namely the South China Sea (LCS), makes Indonesia vulnerable to spillover effects arising from various possible incidents and conflicts in the region. To safeguard its interests, Indonesia must be able to play its strategic role in ensuring a stable, safe and peaceful ASEAN Region during conflicts of interest of other countries in the region. To advance Indonesia's national interests in the region, diplomatic steps taken by Indonesia must be complemented and supported by strategic steps in the defense sector. Indonesia has long adhered to the Total People's Defense and Security System (the Universal People's Defense and Security System, hereinafter referred to as Sishankamrata) as the basis of its national defense policy. Sishankamrata contains core values ​​and principles that guide the formulation and implementation of Indonesia's national defense policy. Sishankamrata is embodied in the doctrine, strategy, and posture of Indonesia's national defense As a strategic defense concept, Sishankamrata must remain relevant and suitable to deal with a volatile, uncertain, complex, and ambiguous strategic environment (VUCA), while at the same time contributing to the advancement of Indonesia's national interests.